Análisis de factibilidad para la implementación de un sistema contable en la compañía INTERDATOS S.A - Cevallos Cortez, Sasha Anahi (2021)
This case study is conducted in the company Interdatos S.A. located in the city of Babahoyo, which is dedicated to the provision of Internet service; the problem that keeps the company lies in the records of its operations and in the execution of the accounting management that the company carries, preventing it from having an adequate control of its activities and in turn does not have accurate knowledge of its financial situation. Due to this, a feasibility analysis will be made for the implementation of an accounting system within the company that will help to improve the execution of its accounting functions achieving effectiveness and efficiency in its processes, allowing a correct control of its administration, with this analysis the feasibility and viability of the implementation of the accounting system will be verified.